National Culture And Employee Participation In Decision-Making In Malaysia: A Conceptual Review - SHAED, MASLINA BINTI MOHAMMED; AZAZI, NOOR ALYANI NOR; SAMSURIJAN, MOHAMAD SHAHARUDIN (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to review the influence of national culture on employee participation in decision-making in the organization. A conceptual review was conducted to identify the existing research and literature on national culture towards employee participation. The articles were searched based on important keywords and relevance. Based on the previous literature, the results suggested that national culture appears as one of the important variables on employee participation in decision-making.